Photoluminescence emission at room temperature in zinc oxide nano-columns - Rocha, L. S. R. [UNESP]; Deus, R. C. [UNESP]; Foschini, C. R. [UNESP]; Moura, F.; Garcia, F. Gonzalez; Simoes, A. Z. [UNESP] (Elsevier B.V., 2014)
Hydrothermal microwave method (HTMW) was used to synthesize crystalline zinc oxide (ZnO) nano-columns at the temperature of 120 degrees C with a soaking time of 8 min. ZnO nano-columns were characterized by using X-ray analyses (XRD), infrared spectroscopy (FT-IR), thermogravimetric analyses (TG-DTA), field emission gun and transmission electron microscopy (FEG-SEM and TEM) and photoluminescence properties (PL). XRD results indicated that the ZnO nano-columns are free of any impurity phase and crystallize in the hexagonal structure. Typical FT-IR spectra for ZnO nano-columns presented well defined bands, indicating a substantial short-range order in the system. PL spectra consist of a broad band at 590 nm and narrow band at 480 nm corresponding to a near-band edge emission related to the recombination of excitons and level emission related to structural defects. These results show that the HTMW synthesis route is rapid, cost effective, and could be used as an alternative to obtain ZnO nano-columns in the temperature of 120 degrees C for 8 min. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Nanostructures; Chemical synthesis; Electron microscopy; Luminescence; Crystal structure